KONSTRUKSI KONSEP HAK ATAS MEREK DALAM SISTEM HUKUM JAMINAN FIDUSIA SEBAGAI UPAYA MENDUKUNG PEMBANGUNAN EKONOMI - Sri Mulyani (Faculty of Law, Universitas Diponegoro, 2014)
Default Paragraph Font;hps;In the development of society in the global market, especially the rights of intellectual property rights to the brands used as collateral (collateral) to obtain bank credit internationally. Purpose of this research to formulate the concept of rights to the brand in a fiduciary legal system in an effort to support economic development. This research is included in the realm of socio- legal studies research study is a study that examines the non-doctrinal law by using the approach of law and social science. Setting Brand as objects in the system guarantees fiduciary law has not given a clear interpretation. The ideal concept of the brand as a fiduciary arrangement should be developed is a comprehensive arrangement, both from a systemic culture of law, the legal structure and the substance of the law based on Pancasila and the 1945 Constitution in economic development.